Efek Pelatihan Sumber Daya Insani terhadap Kinerja Karyawan Dompet Sejuta Harapan - Triana Nur Handayani; Arief Effendy (Pawarta: Journal of Communication and Da'wah, 2024)
Human resources greatly determine the process of successful performance of an organization. Human resource development aims to make it easier to realize organizational goals because quality human resources are capable of carrying out their duties and functions as employees. The importance of human resource training and development within an institution or company is that it is hoped that the employees involved will be able to do their work or have the capability according to competency requirements. So it is necessary to know how human resource training is provided, its performance results, and how strong the influence is on Dompet Sejuta Harapan (DSH) Institute employees. determine the level of human resource training provided, performance results, and how strong the influence is on employees of DSH institutions using quantitative research methods based on concrete data measured using statistics as a calculation test tool. The results of providing training are in the Good category, the Means value is 23.375 in the interval 24-27. The performance results are in the Good category, it is known that the value of 0.621 is between 0.61-0.80, and it is concluded that it has a strong correlation. From the calculation of the r xy correlation, r is 0.870. r table 0.349. Then we get r results from r tables, meaning the hypothesis set can be accepted as true. Based on the results of the data analysis, it can be concluded that the hypothesis that "There is/is a positive influence between human resource training and the performance results of DSH employees" can be accepted as true